Being Subject to Restrictions, Limitations and Disciplining: A Thematic Analysis of Individuals' Experiences in Psychiatric Intensive Care. (3rd July 2017) - Salzmann-Erikson, Martin; Söderqvist, Cecilia
ABSTRACT: The aim of this study was to describe individuals' experiences of being hospitalized in psychiatric intensive care units (PICUs). Four participants who had previously been admitted in a PICU were interviewed using open-ended questions. The data were analyzed using thematic analysis. Analysis resulted in a synthesis of the various ways patients experienced limitations: (1) Descriptions of Being Limited in the Environment, (2) Descriptions of being Limited in Interactions with Staff, (3) Descriptions of Being Limited in terms of Access to Information, and (4) Descriptions of Having Limited Freedom and Autonomy. Hospitalization is experienced as a life-changing event that shows a kaleidoscopic view of limitation. We stress that the conceptualization of limitation must be considered due to its historical origins, sociopolitical aspirations, and philosophy of care. Thus, nurse practitioners and nursing leaders are advised to put the patient's experience at the center of care, and to involve and integrate patients throughout the recovery process.